Modern Approach to Outpatient Surgical Treatment of Transient Paraproctitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
As a result of the study, it was found that the ischiorectal type of acute paraproctitis is 8-10 times more common than other subcutaneous, subcutaneous and pelviorectal types. Relapse in patients with acute paraproctitis was detected in 16.7%. If we take into account the complication of the disease with pararectal fistula, the relapse rate in acute paraproctitis is very high. Therefore, in the ischiorectal, subcutaneous and subcutaneous types of paraproctitis, it is advisable to use the radical method of the operation "opening the purulent cavity, liquidation of the internal opening".